Choice of an Exchange Rate Regime: the Role of Optimum Currency Area Theory - Horvath, Julius (Competitio, 2004)
This lecture deals with the problem of the choice of exchange rate regime for fiat and fully convertible currencies. We begin with a review of different types of exchange rate regimes and discuss the difference between de jure and de facto regimes. We also briefly talk about how classification of exchange rate regimes leads to different interpretations of the relationship between regime and macroeconomic performance. Afterwards we give a short discussion of the vanishing intermediate exchange rate regime hypothesis. In the second part of the lecture we mention five different approaches to the choice of the optimal exchange rate regime and provide a general overview of the literature on optimum currency areas.